Kajian Gaya Kepemimpinan di Instansi Pemerintah Daerah - Rayhan Fadlan; Sakinah Putri Azarah; Shafira Apriananda; Olivia Dwi Ruselda; Shofy Abiyah (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
Leadership is very important and central. In order to achieve common goals, people as part of an agency or organization must promote unity by following leadership instructions. Based on the leader's direction, all differences in desires and wills are ultimately unified and directed into one. Leaders as individuals have motivations that may not align with those of group members, both in terms of their desire to join and unite within the group and in carrying out activities under their obligations and responsibilities. In government institutions, all leaders are key figures who have a significant influence on employees. This research is qualitative in nature, using descriptive interview techniques.